The Impact of Teachers’ Feedback Style and Student Self-Efficacy on Writing Proficiency of Iraqi English Learners - Salwan Adnan Ahmed (مجلة الباحث, 2026)
Examining the relationships between students’ self-perceptions of their writing skills and the methods their English teachers use to provide feedback , this quantitative study examines the experiences of Iraqi college students pursuing English language education. The Teachers’ Feedback Style Scale ( TFSS ) the English Writing Self - Efficacy Scale ( EWSES) and a demographic questionnaire were administered to a sample of 300 Iraqi EFL learners from three public universities. A standardized timed writing test was administered and graded using the updated IELTS rubric to determine the level of writing proficiency. The results showed that there was a favorable association between the style of formative feedback and students’ self - efficacy and writing proficiency as determined by Pearson correlation coefficients and multiple regression analysis